Two new cumaceans (Crustacea: Peracarida) from the South-West Atlantic with remarks on the problematic genus Holostylis Stebbing, 1912 - Roccatagliata, Daniel Carlos (2015)
In 1912-13, Stebbing erected the genera Holostylis and Ekdiastylis for those diastylids with the endopod of the uropods being one- and two-segmented, respectively. The validity of the genus Holostylis is still controversial and the genus Ekdiastylis continues to be suppressed. In the present contribution, two new diastylids are fully described and illustrated: one of them has the endopod of the uropod one-segmented, Holostylis uniramosa n. sp., and the other has the endopod of the uropod two-segmented, Diastylis decalineata n. sp. The genus Holostylis has currently three nominal species, which are easily distinguished from each other by the number of thoracic appendages with fully developed exopods in females: three in H. helleri (Zimmer, 1908), one in H. spinicuadata Błażewicz-Paszkowycz and Heard, 2005, and none in H. uniramosa n. sp. The validity of genus Holostylis is confirmed and its diagnosis emended. Diastylis decalineata n. sp. mainly distinguished from the other species of Diastylis with two-segmented uropod endopods by the shape and sculpture of its carapace.